Anti-inflammatory effects of phenolic-rich cranberry bean (Phaseolus vulgaris L.) extracts and enhanced cellular antioxidant enzyme activities in Caco-2 cells. (November 2017) - Chen, Peter X.; Zhang, Hua; Marcone, Massimo F.; Pauls, Karl Peter; Liu, Ronghua; Tang, Yao; Zhang, Bing; Renaud, Justin B.; Tsao, Rong
Highlights: Abundance of flavonoids in regular-darkening (RR) cranberry bean extract. RR extract displayed strong dose-dependent cellular antioxidant activity. Regular- and non-darkening cranberry bean extract suppressed IL-8 secretion. Both extract also enhanced antioxidant enzyme activity. Abstract: Purified phenolic extracts of cooked regular-darkening (RR) and non-darkening (CND) cranberry beans were evaluated for their phenolic content, antioxidant and anti-inflammatory activity and bioavailability using a human colonic carcinoma (Caco-2) cell model. Major compounds included flavanols such as catechin, epicatechin and proanthocyanidins which were predominant to RR extract. RR and CND both contained p -coumaric acid, ferulic acid and tryptophan. Our results showed strong cellular antioxidant activity in RR and dose-dependent attenuation of TNF-α-induced pro-inflammatory cytokine Interleukin-8 (IL-8) secretion. In addition, the extracts displayed protective benefit to endogenous antioxidant enzymes such as SOD, CAT, GPx and GR as well as GSH. Flavanols displayed poor bioavailability suggesting the beneficial effects occur via adsorption on the cell surface leading to cell signalling and localized radical scavenging activity. Our results support the beneficial effects of cranberry bean phenolics in their ability to ameliorate oxidative stress conditions notably in intestinal inflammatory responses.